Microperc Versus Miniperc for Treatment of Renal Stones Smaller Than 2 cm in Pediatric Patients - Dundar, Gokce; Gokce, Gokhan; Gokcen, Kaan; Korgali, Esat; Asdemir, Aydemir; Kaygusuz, Kenan (Urology Journal, 2016)
Purpose: Pediatric stone disease is an important clinical problem in pediatric urology practice. We aimed to compare mini-percutaneous nephrolithotomy (miniperc) and micro-percutaneous nephrolithotomy (microperc) in pediatric patients who underwent unsuccesful SWL procedure. Materials and methods: A number of 43 pediatric patients, aged 17 years or younger, were treated with miniperc or microperc procedures due to renal calculi by a single surgeon. In group 1, there were 27 patients who underwent miniperc procedure. In group 2, 16 patients were treated by microperc. Results: Mean age of the patients were 9.5 (3-17) years in group 1 and 7.9 (2-16) years in group 2 (P = .25). Stone burden was similar between the two groups. Mean operation duration was 74.1 (40-110) minutes in miniperc group and 37.2 (20-55) minutes in microperc group (P < .01). Patients who underwent microperc were discharged from clinic earlier. Hyperthermia without bacteraemia was observed in 2 children in the miniperc group and was treated by using a single dose of paracetamol and also 2 children in the same group needed blood transfusion. There was a tendency for low haemoglobin decrease in microperc group compared to miniperc (P > .05). Conclusion: The management of pediatric stone disease has evolved with improvements in techniques and minimalisation of surgical instruments and thus, it can be effectively and safely used in children by experienced surgeons.